Knowledge mapping and research trends on rehabilitation of patients with mechanical ventilation in the ICU from 2005 to 2024: a bibliometric analysis via CiteSpace and Bibliometrix - Kang, Xizhen; Tian, Jun; Yang, Yanan; Zhu, Ye; Teng, Hui; Xiao, Huifang; Shu, Qing (Frontiers in Neurology, 2025)
ObjectiveEarly rehabilitation, which refers to multidisciplinary, structured interventions initiated during the acute phase of illness, aimed at promoting physical recovery, reducing disability, and preventing complications, is essential for critically ill patients with mechanical ventilation. To review literature related to early rehabilitation in patients with mechanical ventilation in the intensive care unit, the paper aims to identify research topics and frontiers, report on current research trends, and offer valuable insights and perspectives for future development in the field.MethodsThis study retrieved related publications from the Web of Science Core Collection database on March 12, 2025. After collecting the data, CiteSpace V.6.1. R6 was used to conduct a visual analysis of countries, institutions, authors, cited journals, cited references, and keywords. Bibliometrix 4.1.3 was used to generate the main information, country collaboration map, and three-field plot. The data was visualized through knowledge maps and collaborative networks.ResultsWe obtained a total of 375 articles on early rehabilitation in patients with mechanical ventilation. The number of annual publications has generally shown a steady growth trend in the past 20 years, with an annual growth rate of 21.59%. The United States, Brazil, Australia, and England are major contributing countries. North American and European countries have established the most intensive cooperation networks. Most of the active scholars, institutions, and journals in this field come from the United States, Canada, Australia, and England. Our research shows that ICU-acquired weakness, pulmonary dysfunction, and disorder of consciousness are important issues as well as challenges that need to be addressed urgently.ConclusionThis study analyzed the current status of early rehabilitation in patients with mechanical ventilation in the intensive care unit via CiteSpace and Bibliometrix, then identified the research hotspots and frontiers on it. While current evidence remains limited, methodologically rigorous multicenter randomized controlled trials with large cohorts are warranted to establish robust evidence regarding rehabilitation efficacy in mechanically ventilated patients. Emerging innovations in rehabilitation protocols are anticipated to progressively optimize clinical pathways as research methodologies advance.